2020
DOI: 10.1063/5.0008980
|View full text |Cite
|
Sign up to set email alerts
|

Metal-functionalized 2D boron sulfide monolayer material enhancing hydrogen storage capacities

Abstract: In the present work, we have systematically investigated the structural, electronic, vibrational, and H2 storage properties of a layered 2H boron sulfide (2H-BS) monolayer using spin-polarized density functional theory (DFT). The pristine BS monolayer shows semiconducting behavior with an indirect bandgap of 2.83 eV. Spin-polarized DFT with van der Waals correction suggests that the pristine BS monolayer has weak binding strength with H2 molecules, but the binding energy can be significantly improved by alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
0
19
1
Order By: Relevance
“…Nevertheless, a recent theoretical study predicted that 2D BS exists in several stable phases with unique electronic structures, 24 including superconducting, 14 thermoelectric, 25 and hydrogen storage properties. 26 In this paper, we report the preparation of 2D BS nanosheets by physically exfoliating bulk rhombohedral boron monosulfide (r-BS). Because the synthesis of r-BS has only been reported by a few groups, 27,28,29 we carefully characterized r-BS, including its thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a recent theoretical study predicted that 2D BS exists in several stable phases with unique electronic structures, 24 including superconducting, 14 thermoelectric, 25 and hydrogen storage properties. 26 In this paper, we report the preparation of 2D BS nanosheets by physically exfoliating bulk rhombohedral boron monosulfide (r-BS). Because the synthesis of r-BS has only been reported by a few groups, 27,28,29 we carefully characterized r-BS, including its thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is built by zigzag-like chains of B 3 X 3 rings cross-linked by the rhombic linkers comprising the four-membered B 2 X 2 rings. In addition, considering the versatility of B chemistry (higher coordination than 3 and inherent polymorphism), we also include the BX model, , Figure g, where B–B bonds are formed between trigonal units (Figure f). This structure has been found in III–VI layered compounds such as GaS, GaSe, InS, and InSe.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical predictions indicate that borophene [ 6 , 7 , 8 , 9 ], boron hydride [ 10 ], boron sulfide [ 11 ], boron oxide [ 12 ], and boron phosphide [ 13 ] form stable 2D phases; hence, these structures have attracted much attention as targets for developing new 2D materials [ 14 ]. Among them, rhombohedral boron monosulfide (r-BS) has been successfully synthesized experimentally [ 15 ] and is theoretically predicted to exhibit excellent thermal conductivity [ 16 ] and high hydrogen storage performance via alkali modification [ 17 ]. Moreover, experimental reports have indicated that r-BS can be easily exfoliated from bulk to nanosheets physically in the air [ 18 ].…”
Section: Introductionmentioning
confidence: 99%